Structural characterization of nickel oxide/hydroxide nanosheets produced by CBD technique. (October 2015) - Taşköprü, T.; Zor, M.; Turan, E.
Graphical abstract: SEM images of (a) as deposited β-Ni(OH)2 and (b) NiO samples deposited with pH 10 solution. The inset figures shows the absorbance spectra of (a) β-Ni(OH)2 and (b) NiO samples. Highlights: The formation of β-Ni(OH)2 and NiO were confirmed with XRD, SEM, FT-IR and Raman. Porous nickel oxide was synthesized after heat treatment of nickel hydroxide. The increase in pH value changes the nanoflake structure to hexagonal nanosheet. On increasing the pH from 8 to 11, the band gap decreases from 3.52 to 3.37 eV. Abstract: Nickel hydroxide samples were deposited onto glass substrates using Ni(NO3 )2 ·6H2 O and aqueous ammonia by chemical bath deposition technique. The influence of pH of solution was investigated by means of X-ray diffraction, field emission scanning electron microscopy, Fourier transform infrared, Raman spectroscopy, optical absorption and BET analysis. The as-deposited samples were identified as β-Ni(OH)2, were transformed into NiO after heat treatment in air at 500 °C for 2 h. Porous nickel oxide nanosheets are obtained by heating nickel hydroxide nanosheets. The optical transitions observed in the absorbance spectra below optical band gap is due to defects or Ni 2+ vacancies in NiO samples. The band gap energy of NiO samples changes between 3.37 and 3.52 eV depending on the pH values.